Mechanoluminescent-energy harvesting bimodal sensors for self-powered communication sensors - Sugato Hajra; Swati Panda; Kushal Ruthvik Kaja; Seongkyu Song; Yeonkyeong Ryu; Basanta K. Panigrahi; Naratip Vittayakorn; Ju Hyuck Lee; Soon Moon Jeong; Hoe Joon Kim (Journal of Materials Chemistry C, 2025)
A wearable ML+PENG platform using ZnS:Cu in a PDMS polymer matrix, generating light and electrical energy from bending for self-powered underwater communications.
Keywords: Mechanical and Optical Resonators; Polydiacetylene-based materials and applications; Advanced Chemical Sensor Technologies